Response of ligninolytic macrofungi to the herbicide atrazine: dose-response bioassays - Wilberth Chan Cupul; Gabriela Heredia Abarca; Refugio Rodríguez Vázquez; Dulce Salmones; Rigoberto Gaitán Hernández; Enrique Alarcón Gutiérrez (Revista Argentina de Microbiología, 2014)
The effect of atrazine concentrations on mycelial growth and ligninolytic enzyme activities of eight native ligninolytic macrofungi isolated in Veracruz, México, were evaluated in a semi-solid culture medium. Inhibition of mycelial growth and growth rates were significantly affected (p = 0.05) by atrazine concentrations (468, 937, 1875, and 3750 mg/l). In accordance with the median effective concentration (EC50), Pleurotus sp. strain 1 proved to be the most tolerant isolate to atrazine (EC50 = 2281.0 mg/l), although its enzyme activity was not the highest. Pycnoporus sanguineus strain 2, Daedalea elegans and Trametes maxima showed high laccase activity (62.7, 31.9, 29.3 U mg/protein, respectively) without atrazine (control); however, this activity significantly increased (p < 0.05) (to 191.1, 83.5 and 120.6 U mg/protein, respectively) owing to the effect of atrazine (937 mg/l) in the culture medium. Pleurotus sp. strain 2 and Cymatoderma elegans significantly increased (p < 0.05) their manganese peroxidase (MnP) activities under atrazine stress at 468 mg/l. The isolates with high EC50 (Pleurotus sp. strain 1) and high enzymatic activity (P. sanguineus strain 2 and T. maxima) could be considered for future studies on atrazine mycodegradation. Furthermore, this study confirms that atrazine can increase laccase and MnP activities in ligninolytic macrofungi.